Accounting discretion, loan loss provisioning, and discipline of Banks’ risk-taking - Bushman, Robert M.; Williams, Christopher D. (Journal of Accounting and Economics, 2012)
Examining banks across 27 countries, we estimate two measures of the forward-looking orientation reflected in discretionary loan provisioning practices within a country. We document that forward-looking provisioning designed to smooth earnings dampens discipline over risk-taking, consistent with diminished transparency inhibiting outside monitoring. In contrast, forward-looking provisioning reflecting timely recognition of expected future loan losses is associated with enhanced risk-taking discipline. Thus, proposals to change loan loss accounting embed significant risks of unintended consequences, as gains from reducing pro-cyclicality may be swamped by losses in transparency that dampen market discipline and increase the scope for less prudent risk-taking by banks.